Remotely-sensed slowing down in spatially patterned dryland ecosystems - Veldhuis, M.P.; Martínez Garcia, R.; Deblauwe, V.; Dakos, V. (Wiley, 2022)
Regular vegetation patterns have been predicted to indicate a system slowing down and possibly desertification of drylands. However, these predictions have not yet been observed in dryland vegetation due to the inherent logistic difficulty to gather longer-term in situ data. Here, we evaluate the theoretical prediction that regular vegetation patterns are associated with empirically derived temporal indicators (autocorrelation, variance, responsiveness) of critical slowing down in a dryland ecosystem in Sudan using different remote sensing products.